Kelimpahan Dead Coral with Algae di Terumbu Karang Pulau Gili Noko, berdasarkan Faktor Oseanografi - Farilla Intan Kurnia Rizky; Nirmalasari Idha Wijaya; Supriyatno Widagdo (Samakia : Jurnal Ilmu Perikanan, 2025)
The condition of coral reefs on Gili Noko Island has decreased due to climate change and human activities. The initial survey results showed a medium damage category on coral reefs and the dominance of Dead Coral with Algae (DCA). This research was conducted in the waters of Gili Noko Island, Bawean which was divided into 4 stations with the aim of describing oceanographic conditions, describing DCA characters and analyzing various factors that cause DCA abundance on Gili Noko Island. This research was conducted from November 2024 to July 2025. The method used was the Underwater Photo Transect (UPT) method to see the percentage of coral cover. Coral cover abundance data were analyzed using Coral Point Count with Excel Extensions (CPCe) software. Data on oceanographic parameters and water quality were taken in situ and tested in the laboratory using the UV Vis spectrophotometer method to see the content of nitrate and phosphate. The research data were analyzed using Principal Component Analysis (PCA) to determine the correlation between DCA abundance and physico-chemical water quality parameters. The results showed that the physico-chemical parameters reflect the tropical waters of Gili Noko Island and support the life of marine organisms including coral reefs. DCA abundance was found at all observation stations with the highest abundance at station 1 at 48.3%. This was caused by the high nitrate concentration of 0.2532 mg/L. DCA abundance on coral reefs is dominated by turf algae or benthic macroalgae. The PCA correlation results showed the DCA abundance factor was influenced by nitrate concentration.